Exploración paleopatológica en los restos óseos de inmigrantes chinos inhumados en Huaca Bellavista a fines del siglo XIX - Irureta Salvatierra, Gonzalo V.R. (2021)
The arrival and establishment of the Chinese community in Peru during the 19th century was a very relevant event within its historical context, having a considerable impact on sociocultural aspects of the country until the present. An important source of knowledge about this foreign population is the discovery of human remains identified as Chinese immigrants buried in the Huaca Bellavista Archaeological Site, formerly part of the Zavala hacienda, located in the Santa Anita district, in the province of Lima. In this sense, the present research will approach the study of this sample with an epidemiological orientation, emphasizing the recurrence, degree of expression and distribution of various pathological and traumatic alterations in the dental record that reflect the levels of health that these individuals would have experienced inside and outside the Zavala hacienda, in order to have a better understanding of the prevailing conditions of life and death of this population. Providing, as a result, evidence of continuous forced labor and, above all, precarious circumstances of subsistence; corroborating and complementing in this way the preceding documentary information on the lifestyle to which Chinese immigrants were subjected during their labor in the various haciendas of the Peruvian coast.